Metamorfosis Ibadah Kurban Dalam Al-Qur`an - Faridah, Durrotul (ojs.unsiq.ac.id, 2016)
Kurban ritual is a series of worship that has historical roots in the peoples earlier. A series of processes that form the sacriﬁ cial metamorphosis cycle that can be described with attention to the periodization of the development of forms of sacriﬁ ces from time to time, which is based on the verses of the Koran and also a history text that speaks sacriﬁ ces. In writing this essay the author uses several methods of research, both to obtain data or analyze the data, namely: library research, sources of primary data, secondary data and tertiary data sources. As for the collections of data by the method of thematic interpretation and in analyzing the data the author uses speculative philosophy of history. The results showed that the metamorphosis of sacriﬁ cial worship in the Qur’an (thematic studies) can know the journey of sacriﬁ ces from time to time and can show how the essence of it in syari’atkan sacriﬁ ces, so that it is expected to apply the values contained therein.